Numerical simulation of out-of-plane distortion fatigue crack growth in bridge girders - Miller, Paula A., author; Mahmoud, Hussam, advisor; Heyliger, Paul, committee member; Strong, Kelly, committee member (Colorado State University. Libraries, 2014)
Aging of the United States infrastructure systems has resulted in the degradation of many operational bridge structures throughout the country. Structural deficiencies can result from material fatigue caused by cyclical loadings leading to localized structural damage. While fatigue crack growth is viewed as a serviceability problem, unstable crack growth can compromise the integrity of the structure. Multi-girder bridges designed with transverse cross bracing systems can be prone to distortion fatigue at unstiffened web gaps. Cracking is exhibited within this fatigue prone region from the application of cyclical multi-mode loadings. Focus of fatigue analysis has largely been directed at pure Mode I loading through the development of AASHTO fatigue classifications for crack initiation and the Paris Law for crack propagation. Numerical modeling approaches through the ABAQUS Extended Finite Element Method offers a unique avenue in which this detail can be assessed. Finite element simulations were developed to first evaluate the applicability of the Paris Law crack propagation under multi-mode loading against experimental data. Following the validation, fatigue crack growth in plate girders with various web gap sizes was assessed due to mixed-mode loadings. Modeling results showed enlargement of horizontal initial crack lengths within stiffer web gap regions arrested crack development. Crack directionality was also seen to change as initial crack lengths were increased. From this research it is hypothesized that deterioration of the transverse stiffener connection can be minimized by increasing the horizontal length of initial fatigue cracks. Enlargement of the crack plane away from regions of localized stress concentrations within the web gap may result in arrestment of the out-of-plane distortion induced cracking.
Keywords: ABAQUS XFEM; rehabilitation; numerical analysis; fatigue and fracture; crack propagation